2021
DOI: 10.1161/circep.121.010375
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-Field Ablation in Ventricular Myocardium Using a Focal Catheter

Abstract: Background - Pulsed-field ablation (PFA) is a rapid and nonthermal energy with higher selectivity to myocardial tissue in comparison to radiofrequency ablation (RFA). However, its effects on ventricular myocardium, and titration of lesion dimensions have not been well studied. This study examined the effect of PFA on ventricular myocardium, and the influence of application repetition on lesion dimensions. Methods - An 8Fr lattice catheter with a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…Lesion dimensions progressively increased with increased repetitions (2, 3, and 4 repeats), with the depth increasing from 4.2±1.0 mm (2× repetitions) to 6.1±2.1 mm (4× repetitions; P =0.003). This confirms and elaborates previous findings by both our group and recently by Yavin et al, 7 who demonstrated improved depth by comparing 1 application against 4 repeat applications.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Lesion dimensions progressively increased with increased repetitions (2, 3, and 4 repeats), with the depth increasing from 4.2±1.0 mm (2× repetitions) to 6.1±2.1 mm (4× repetitions; P =0.003). This confirms and elaborates previous findings by both our group and recently by Yavin et al, 7 who demonstrated improved depth by comparing 1 application against 4 repeat applications.…”
Section: Discussionsupporting
confidence: 93%
“…As previously described, this 7.5F bidirectionally-deflectable catheter has a tip containing 9 mini-electrodes/temperature sensors and location sensors allowing for 3-dimensional localization. 4 , 5 , 7 PFA is applied as a monopolar field from the entire lattice tip (to a grounding electrode) using a proprietary biphasic waveform. The catheter is irrigated at 4 and 15 mL/min at baseline and during ablation, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…62,63 Preliminary results in patients with atrial fibrillation are exciting 64,65 and animal experiments for VT ablation have also shown encouraging results. 66 In summary, the promising early experience with irreversible electroporation suggests that soon, catheter ablation of VT could be more efficacious and probably safer. Such improvement may heavily influence the refinement or the need for SBRT in VT management.…”
Section: Sbrt In Ventricular Tachycardiasmentioning
confidence: 99%
“…Even a subtherapeutic, single delivery of PFA can cause electrograms to disappear. Furthermore, data has shown that repetitive applications 10 are required to “push” the depth of the lesion to its maximum – explaining the eight pre‐determined applications that were delivered per site in this manuscript. But how does an operator assess when enough deliveries have been placed?…”
mentioning
confidence: 96%